(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article is dedicated to the role and effectiveness of learning English with usage of specific teaching methods and in this article we investigated the compatibility of the concept of foreign language environment that helps individuals and groups become more effective in work to introduce ways of presenting theoretical view with practical part and construct a good lexical base for the learners who study English.